The GravyTrain toolbox for molecular cell biology - Oren Shatz; Zvulun Elazar (PLoS ONE, 2025)
Yeast genetics has the power for thorough investigation of complex systems in molecular cell biology. Here, we present GravyTrain, a comprehensive repository of constructs for genomic modifications, including gene deletions or tagging with fusion tags for robust protein characterization and manipulation. The modular cloning scheme employed by GravyTrain allows shuffling of elements between constructs and potentially the application of included protein tags to research beyond yeast. The experimental potential of GravyTrain is demonstrated by the de novo construction of a library of strains for studying autophagy in yeast.